Linear stability analysis of short journal bearing with an axial groove: Lineare Stabilitätsanalyse von Kurzgleitlagern mit einer axialen Nut - Hamdavi, S. (Wiley-VCH Verlag, 2017)
The aim of this paper is to investigate the effect of one axial groove at the inlet of full film bearing surface on dynamic coefficients and linear stability of rotor-bearing systems supported by two short journal bearings. The DuBois-Ocvirk short bearing approximation is applied to the governing Reynolds equation. The linearized nondimensional dynamic coefficients of stiffness and damping are calculated for both plain and grooved journal bearings. Moreover, using the linear stability analysis, the whirl frequency ratio and the threshold speed are obtained. Finally, results are presented for various eccentricity ratios, groove depth, and groove width a slenderness ratio of L/D=0.25. The results appeal that dynamic coefficients are mostly affected significantly at low eccentricity ratio regions. In sequence, one axial groove causes a remarkable deviation in the values of threshold speed and whirl frequency ratio. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim